Between the church and the marketplace: how professional gospel musicians negotiate the tension between sacred and market contexts, with reference to the case of No Limits, a vocal music group from Soweto - Moshugi, Kgomotso Samuel (My University, 2016)
The music industry as a sector of cultural industries provides an environment for musicians to engage with the business of music. Churches, as religious and social environments, provide a platform for musical activity and development for musicians. While the church has provided musical development, the music industry has been looked to for sustaining musical careers. Using the adaptation of the Landry value chain model, this research highlights difficulties and successes that No Limits, a South African music group, has encountered in pursuing a professional career in sacred and marketplace contexts. In turn, this has revealed management and general administrative issues that independent musicians commonly face in their pursuit of a professional career. The study observes how professional gospel musicians handle the tension between the sacred and market contexts based on the assumption that these contexts have varying operating systems and thus present a difficulty for professional musicians seeking to operate in both contexts. The introductory chapter and the literature review provide the background and context for the study, the relevant historical information and the Seventh-day Adventist church context. A detailed narrative of the development of No Limits is provided in the fourth chapter leading to the analysis presented in the fifth chapter, which expands on specific moments and issues discussed in the narrative within Charles Landry’s framework of a value chain. His model suggests an integration of all the activities in the value chain in order to succeed in cultural pursuits. These entail beginnings, production, circulation, delivery mechanisms and audience reception (with feedback). No Limits was, therefore, analysed in terms of this model. Key findings point to the difficulty associated with the professionalisation of the music occupation, of seeking to be altruistic and sustainable at the same time. Also, that social and cultural value of devotional content from the sacred context and the material economic demands from the marketplace characterise the fundamental tensions for musicians pursuing existence in these contexts. The Seventh-day Adventist church, in which No Limits was incubated, provided the immediate context for this study and the data was collected through an analysis of archives, discography and interviews with different individuals in the No Limits value chain. Key words: marketplace,
A research report submitted to the Faculty of Humanities, University of the Witwatersrand, in fulfilment of the requirements of the degree of Masters in Arts, Culture and Heritage Management
Keywords: Cultural industries; Music trade; Popular music; Church music